CO2 Capture From Air in a Radial Flow Contactor: Batch or Continuous Operation? - Schellevis, Michel; Jacobs, Tim; Brilman, Wim (Frontiers in Chemical Engineering, 2020)
The capture of CO2 from the atmosphere via Direct Air Capture using solid supported-amine sorbents is an important option to reduce the atmospheric concentration of CO2. It addresses CO2 emissions from dispersed sources and delivers a location independent sustainable carbon source. This study evaluates the possibility for a continuous adsorption process for direct air capture in a radial flow contactor, using both batch and continuous mode of operation. Gas and solids flow were varied to determine hydrodynamic feasible operating conditions. The operation modes are compared by their capture efficiencies in the optimal adsorption time range of 0.5 t_sto^B and 1.5 t_sto^B. A 15-25% lower capture efficiency is found for a continuous process compared to a batch process in the relevant range for direct air capture. This decline in gas-solid contact efficiency is more pronounced at longer adsorption time and higher superficial gas velocity. Overall, a batch process is preferred over a continuous process in the majority of operating conditions.